2017
DOI: 10.5037/jomr.2017.8203
|View full text |Cite
|
Sign up to set email alerts
|

Association between Tooth Agenesis and Skeletal Malocclusions

Abstract: ObjectivesThe aim of this study was to evaluate the association between tooth agenesis and skeletal malocclusions in Brazilian non-syndromic orthodontic patients.Material and MethodsPretreatment orthodontic records of 348 patients of both genders and with various skeletal malocclusions were examined. Tooth agenesis was evaluated in panoramic radiographs. Angular measurements were taken from lateral cephalometric radiographs to classify the patient’s malocclusion as skeletal Class I, Class II and Class III. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 40 publications
2
22
0
2
Order By: Relevance
“…While this is consistent with the findings of some studies [10,12], other studies have indicated that Class III patients have a higher prevalence of agenesis of teeth other than the M3s than their patients with TA [9]. Costa et al [11] have found Class III malocclusions to be significantly associated with the agenesis of the premolars, Celikoglu et al [15] found this to be the case with the MxI2s.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…While this is consistent with the findings of some studies [10,12], other studies have indicated that Class III patients have a higher prevalence of agenesis of teeth other than the M3s than their patients with TA [9]. Costa et al [11] have found Class III malocclusions to be significantly associated with the agenesis of the premolars, Celikoglu et al [15] found this to be the case with the MxI2s.…”
Section: Discussionsupporting
confidence: 83%
“…Several studies have found no significant differences in the prevalence of TA among different sagittal jaw relationship groups [10][11][12]. Others have reported that agenesis of the M3s depends on sagittal skeletal malocclusion [5] and that TA is significantly less common in skeletal Class II malocclusions [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Por outro lado, a cefalometria é o método que estuda as dimensões do crânio e da face, sendo amplamente utilizada nos estudos em Ortodontia que visam analisar as variações individuais nas dimensões maxilares e mandibulares (Li et al, 2010;Costa et al, 2017;Cruz et al, 2017).…”
Section: Coleta De Materials Biológico Para Extração E Quantificação Dunclassified